‘Whose role is it anyway?’ Experiences of community nurses in the delivery and support of oral health care for older people living at home: a grounded theory study - Gary Mitchell; Patrick Stark; Christine Brown Wilson; Georgios Tsakos; Paul Brocklehurst; Caroline Lappin; Barry Quinn; Nicola Holland; Gerry McKenna (BMC Nursing, 2023)
Abstract Background Older people who receive care at home are likely to require support with oral health care. Community nurses, who are also referred to as district or home care nurses, have an important role with this population. This is because they are the healthcare professionals who are most likely to encounter this population, who may also not be receiving regular dental care or oral health promotion. However, few studies have explored community nursing experiences in the delivery and support of oral healthcare for older people living at home. Methods A grounded theory approach was used to explore experiences of community nurses in the delivery and support of oral health care for older people living at home. Fifteen practising community nurses from the United Kingdom participated in one-to-one semi-structed interviews from May 2021 to December 2021. These interviews were audio-recorded, transcribed verbatim and analysed using constant comparative analysis. Ethical approval was obtained for this study prior to data collection. Results Four categories emerged from the data to support development of the core phenomena. These four categories were: (1) Education, in relation to what community nurses knew about oral health, (2) Practice, with regards to how community nurses delivered oral health care to older people in their own home, (3) Confidence, with consideration to the extent to which this supported or impeded community nurses in providing oral healthcare to older people and (4) Motivation, in terms of the extent to which community nurses thought they could or should influence future practice improvement in the area. The core category was (C) Uncertainty as it was both present and central across all four categories and related to community nursing understanding about their specific role, and the role of other professionals, with reference to oral health of their patients. Conclusions This study reveals community nurses' uncertainty in providing oral healthcare to older adults at home. Emphasising comprehensive and continuous oral health education can boost nurses' confidence in patient support. Interprofessional collaboration and clear role definitions with oral health professionals are crucial for improving oral health outcomes in this vulnerable population.